1986
DOI: 10.1002/j.2050-0416.1986.tb04371.x
|View full text |Cite
|
Sign up to set email alerts
|

Mobilisation of Endospermal Reserves During the Germination of Barley

Abstract: The metabolism of the germinating barley seed is a complicated physiological process. From the point of view of industrial malting, the syntheses of amylolytic and proteolytic enzymes as well as the degra dation of endospermal structures are extremely important. In order to control his process the maltster needs to have a good understanding of these processes as well as of the regulatory mechanisms which control them. When a good malting barley is allowed to germinate under traditional conditions for the time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1

Year Published

1987
1987
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(41 citation statements)
references
References 69 publications
2
38
1
Order By: Relevance
“…It has been widely reported that cysteine and metallo proteinases, the same proteinases indicated for barley adjunct wort from our research, had a high correlation to wort FAN levels in all-malt wort 7,8,10,12,13,23 . These similar consequences from two different production processes seem to conflict at first sight.…”
Section: Why Are Proteinase Activities That Contribute To Fan Productsupporting
confidence: 71%
See 1 more Smart Citation
“…It has been widely reported that cysteine and metallo proteinases, the same proteinases indicated for barley adjunct wort from our research, had a high correlation to wort FAN levels in all-malt wort 7,8,10,12,13,23 . These similar consequences from two different production processes seem to conflict at first sight.…”
Section: Why Are Proteinase Activities That Contribute To Fan Productsupporting
confidence: 71%
“…Thirteen different commercial malts from North America and Europe and two malt samples produced in our laboratory were used for wort FAN and proteinase activity analysis (Table I, No. [1][2][3][4][5][6][7][8][9][10][11][12][13][14]20). Four different malting grade barleys were used for wort FAN analysis (Table I, No.…”
Section: Experiments Materialsmentioning
confidence: 99%
“…This means that among other factors that infl uence amylase production by sorghum during malting is the grain genetic property which was evident in the mean α-amylase activity values obtained for all the sorghum cultivars (Table 2). β-Amylase activity: β-Amylase, the sarccharifying malt-enzyme is an exo-enzyme and attack the amylose chain from the non-reducing end liberating β-maltose which has the free hydroxyl group in β-confi guration (Enari and Sopanen 1986). The low level of β-amylase in sorghum is an important physiological difference between sorghum malt and barley malt.…”
Section: Resultsmentioning
confidence: 99%
“…The importance of these enzymes follows from the fact that the grain has no storage capacity for free amino acids 7,17,20 . During initial embryo development, the grain must provide all the amino acids for the synthesis of hydrolytic enzymes and other essential nitrogenous compounds for sustaining and the continuation of germination 7 . Furthermore, the proteinases facilitate the breakdown of the cell walls and the freeing of starch granules and the release and activation of ␤-amylase 8,21 .…”
Section: -2863(9'8-32mentioning
confidence: 99%
“…Endoproteinases are considered to be the key limiting proteolytic activity enzymes amongst the proteinases 7,23 .…”
Section: -2863(9'8-32mentioning
confidence: 99%